Vitamin D as a novel regulator of tumor metabolism: insights on potential mechanisms and implications for anti-cancer therapy - Abu El Maaty, Mohamed A.; Wölfl, Stefan (International journal of molecular sciences, 2017)
1,25-dihydroxyvitamin D3 [1,25(OH)2D3], the bioactive form of vitamin D, has been shown to possess significant anti-tumor potential. While most studies so far have focused on the ability of this molecule to influence the proliferation and apoptosis of cancer cells, more recent data indicate that 1,25(OH)2D3 also impacts energy utilization in tumor cells. In this article, we summarize and review the evidence that demonstrates the targeting of metabolic aberrations in cancers by 1,25(OH)2D3, and highlight potential mechanisms through which these effects may be executed. We shed light on the ability of this molecule to regulate metabolism-related tumor suppressors and oncogenes, energy- and nutrient-sensing pathways, as well as cell death and survival mechanisms such as autophagy.